A Phase I Study to Evaluate the Safety, Tolerability, and Pharmacokinetics of Novel Intravenous Formulation of Meloxicam (QP001) in Healthy Chinese Subjects - Ma J; Huang J; Zou C; Wu Q; Xie J; Zhang X; Yang X; Yang S; Wu Z; Jiang Y; Yu S; Zhang X; et al. (Dove Medical Press, 2023)
Junlong Ma,1,2,* Jie Huang,1,* Chan Zou,1 Qian Wu,1 Jinlian Xie,1 Xingfei Zhang,1 Xiaoyan Yang,1 Shuang Yang,1 Ziteng Wu,3 Yan Jiang,3 Sen Yu,3 Xuqing Zhang,4 Guoping Yang,1,5 Mingyuan Li1 1The Third Xiangya Hospital, Central South University, Changsha, Hunan, 410013, People's Republic of China; 2Taihe Hospital, Hubei University of Medicine, Shiyan, Hubei, 442000, People's Republic of China; 3Nanjing Delova Biotech Co., Ltd., Nanjing, Jiangsu, 210042, People's Republic of China; 4King-eagle Med Co., Ltd., Changsha, Hunan, 410013, People's Republic of China; 5Xiangya School of Pharmaceutical Sciences, Central South University, Changsha, Hunan, 410013, People's Republic of China*These authors contributed equally to this workCorrespondence: Mingyuan Li, Email lmyuan3@126.comBackground: Meloxicam is a selective cyclooxygenase-2 inhibitor used for pain relief, but its poor solubility limits its clinical applications. QP001 is a novel intravenous formulation of meloxicam developed with PEG and pH regulator to improve its solubility. This study aimed to evaluate the safety, tolerability, and pharmacokinetics of QP001 in Chinese healthy subjects.Methods: The trial consisted of three parts. Part I was a two-period crossover study to evaluate bioavailability, in which 10 healthy were either intravenously infused with 15mg QP001 (test) or orally given 15mg MobicⓇ (reference). Part II was a single-arm design to assess the pharmacokinetic (PK) characteristics after 30 mg single- and multiple-dose QP001 in 10 subjects. In part III, we investigated the PKs and tolerability of QP001 at a high dose (60 mg) in another 10 subjects. The PK parameters and treatment-emergent adverse events (TEAEs) were evaluated.Results: A total of 30 subjects were enrolled in the study. QP001 was well tolerated and safe without significant TEAEs in all three study parts. The PK characteristics of QP001 were linear following a single-dose range of 15- 60 mg (Cmax and AUC0-t were 5.82- 17.66 μg/mL and 58.08- 251.17 μg∙h/mL, respectively). After five consecutive daily 30 mg doses, the accumulation index was around 1.98, which indicated a minimal accumulation of QP001. Compared to the tablet dosage form, the relative bioavailability of QP001 reached 116.85%. Additionally, the PK profile of QP001 showed no gender difference.Conclusion: QP001 was well tolerated in healthy Chinese subjects after single ascending doses up to 60 mg and multiple-dose of 30 mg. Based on the PK and safety results, QP001 is a promising once-daily intravenous COX-2 inhibitor candidate for managing pain.Trial Registration: The trial is registered at chinadrugtrials.org.cn (ChiCTR2100047884).Keywords: meloxicam, phase I trial, pharmacokinetic, safety, novel formulation